The last magician - Maxwell, Lisa, 1979- (Simon Pulse, 2017)
In an alternate version of present-day Manhattan, magic is dying, and Esta, a Mageus with a talent for manipulating time, travels back to 1901 to stop the destruction of a book that can possibly restore magic, but in Old New York, Esta must navigate gangs, secret societies, and her feelings for another magician in order to save the future of magic.